Inclusive Teaching Strategies for Discipline-based English Studies : Enhancing Language Attainment and Classroom Interaction in a Multicultural Learning Environment - Sit, Hing Wa (Helena) (Springer Singapore : Imprint: Springer, 2017)
This book presents empirical findings that reveal various teaching strategies and responses from two sub-cultural groups of students, i.e. local Hong Kong and Mainland students, with regard to their English studies. It puts forward a constructive model for innovative teaching strategies to enhance language attainment and classroom interaction in a multicultural learning environment in Hong Kong. It highlights inclusive teaching strategies with instructional, inspirational and interactional components to accommodate diverse learners and promote their classroom interaction. In addition to contributing to innovation in higher education in Hong Kong, the lessons learned here can be universally applied to ESL/EFL teaching and education reform around the world. Further, they support better learning and teaching at universities in the context of internationalization. The book will above all benefit undergraduate students in ESL/EFL teacher training programs, and post-graduate research students in applied linguistics, language education and second language teacher education. It also offers a valuable reference book for university lectures in teacher education, researchers in higher education in China, and TESOL/TEFL instructors in English-speaking countries (the UK, USA, Canada, Australia, New Zealand etc.).
Keywords: Linguistics.; Applied linguistics.; Language and languages -- Study and teaching.; elektronické knihy; electronic books